RANCANG BANGUN APLIKASI KAMUS BAHASA SUMBAWA BERBASIS ANDROID - Nora Dery Sofya; Shinta Esabella; Rodianto Rodianto (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2017)
The purpose of this writing is to design and to develop an application that is able to present data in Sumbawa Language (Basa Samawa) Dictionary which is still in book outline into digital form. Spiral method is used in this research for software development process and its data collection method applies literature study with data source from "Dictionary of Sumbawa-Indonesia" by Department of Education National Language Center Office Province of West Nusa Tenggara, moreover its test method pertains black box method that is a software experiment in terms of its functionality. The results of research that has been built with Android Studio 1.5 and SQLite database with target android version 6.0 (Marshmallow) has been accessible through Play Store, in which this application has been equipped with vocabulary search including sentence examples, introduction to dictionary usage, dictionary procedure information and application to contribute to the indigenous communities of Sumbawa as well as exterior societies of Sumbawa in studying Sumbawa language and preserving the Sumbawa cultural heritage.